A Survey to Assess Clinical Pharmacy Services in Makkah County Hospitals, Saudi Arabia - Yosra Al-hindi; Sahar El-ashmony (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background:The services of clinical pharmacy is not included for science purposes only;it includes wide variety of public care and patient engagements. Makkah is a holy city in a developing country which indeed can improve their clinical pharmacy services perspectives.Objectives:Our main objectives were appraising therule of clinical pharmacy services in Makkah. Materials: This was done bysurvey questionsfor clinical pharmacists in Makkah county hospitals.Results: Our data showed that most coverage of clinical pharmacy services on both the scale ofdepartment is 17.14 percent and the scale of patients is 13.2 percent, that means the service does not cover the exact rule of clinical pharmacists. About 57.7 percent of the county hospitals, the pharmacists did not meet the requirement, and the numberwas smaller than in other hospitals.Conclusion:Our data showed that there is a very small percentage of the services of clinical pharmacy as well as the software, hardware.Moreover, there was a huge gap in the teaching methods.